Juridical Analysis of Relationship Between Beneficial Owner Concept & Implementation of Double Taxation Avoidance Agreement (Case Study of Decision Number 736/B/PK/PJK/2013) - Angelica, Bernicia (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
The concept of beneficial ownership emerged in the 1977 OECD Model to address tax issues, specifically to identify the true recipients of passive income such as dividends, interest, and royalties for tax deduction purposes. This concept distinguishes between legal owners and those who actually control and benefit from income. Globalization has increased cross-border transactions, creating both positive impacts, like increased tax revenue, and negative impacts, such as tax avoidance and international double taxation. Double Taxation Avoidance Agreements (DTAA) aim to mitigate these issues by delineating tax responsibilities between countries. In Indonesia, the beneficial owner concept was incorporated into tax regulations to prevent treaty abuse and ensure appropriate tax benefits. This study analyzes Judicial Review Decision Number 736/B/PK/PJK/2013, focusing on the case of PT Indosat Tbk and Indosat Finance BV (IFC BV) regarding the determination of beneficial ownership for tax purposes. The findings indicate that IFC BV met the beneficial owner criteria, thus entitled to DTAA benefits, exempting it from Indonesia's Income Tax Article 26 withholding. The case underscores the importance of clear beneficial ownership determination in international tax agreements to prevent abuse and ensure fair taxation.